Saccade plan overlap and cancellation during free viewing. (October 2016) - Wu, Esther X.W.; Chua, Fook-Kee; Yen, Shih-Cheng
Highlights: A novel method to examine saccade plans during free viewing is proposed. Saccade plans can overlap in time during the free-viewing of images. Saccade plans can be cancelled before they are completed during free viewing. Abstract: In the current study, we examined how the saccadic system responds when visual information changes dynamically in our environment. Previous studies, using the double-step task, have shown that (a) saccade plans could overlap, such that saccade preparation to an object started even while the saccade preparation to another object was ongoing, and (b) saccade plans could be cancelled before they were completed. In these studies, saccade targets were restricted to a few, experimenter-defined locations. Here, we examined whether saccade plan overlap and cancellation mechanisms could be observed in free-viewing conditions. For each trial, we constructed sets of two images, each containing five objects. All objects have unique positions. Image 1 was presented for several fixations, before Image 2 was presented during a fixation, presumably while a saccade plan to an object in Image 1 was ongoing. There were two crucial findings: (a) First, the saccade immediately following the transition was sometimes executed towards objects in Image 2, and not an object in Image 1, suggesting that the earlier saccade plan to an Image 1 object had been cancelled. Second, analysis of the temporal data also suggested that preparation of the first post-transition saccade started before an earlier saccade plan to an Image 1 object was executed, implying that saccade plans overlapped.